A systematic literature review on the formation of global diversity-anti-bullying character in Madrasah students - Astuti, Mirna; Hapipah, Nor; Shaleh, Shaleh (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2025)
Education is the foundation of human life that cannot be separated from the lifelong learning process. However, education today is often focused on cognitive aspects, neglecting the importance of character and moral formation. Phenomena such as bullying in schools show the low and real moral degradation among students, even though they have good academic achievements. This article examines the role of Islamic religious education in shaping the character of global diversity in Madrasah Ibtidaiyah, by emphasizing the importance of moral and spiritual values in education. Through this approach, it is expected that students will not only become intelligent individuals but also have noble characters and are able to get along well in society and in the school environment. This research uses the Systematic Literature Review method to explore relevant literature, and the results show that character education based on religious values can overcome the problem of negative behavior among students. Thus, Islamic religious education plays an important role in creating a generation that is not only intellectually intelligent but also has high moral integrity.